Low-income Housing in Chinese Cities: Policies and Practices - Huang, Youqin (The China quarterly (London), 2012)
This paper argues that the low-income housing programme in China has so far failed to provide adequate housing for the poor for three main reasons: the central government's failure to define a clear mission; a lack of commitment from local governments; and an exclusionary policy towards migrants. A systematic review of low-income housing policy in China shows that the central government juggles its economic and socio-political goals thereby causing constant changes in low-income housing policy. Meanwhile, the existing public finance system, the performance evaluation system and localization in policy implementation have all resulted in a lack of commitment from local governments to low-income housing. Inadequate provision is made worse by problems with allocation. Despite encouraging changes since 2010, many factors underlying the government's failures remain unchanged, thus the fate of low-income housing remains uncertain.